Do Nasal Anatomical Variations Affect the Maxillary Sinus? A CBCT Volumetric Analysis - Mostafa, Raghdaa A.; Samir, Sahar M. (UI Scholars Hub, 2023)
Objective: This study aimed to determine the effect of the concha bullosa (CB) and the nasal septum deviation (NSD) on the volume of the maxillary sinuses using ITK-SNAP (http://www.itksnap.org/ download/snap/). Methods: A total of 70 CBCT scans were analyzed. Three groups were evaluated; control (absence of CB), unilateral CB, and bilateral CB. Moreover, scans were classified according to the NSD into control (no deviation), mild, moderate, and severe NSD deviation. The volume of each maxillary sinus was calculated using the ITKSNAP. Intra-observer reliability analysis was performed by paired-sample t-test. Analysis of variance ANOVA and t-test were used to compare the mean bilateral maxillary sinus volumes. Results: Intra-observer reliability for the maxillary sinus volume exhibited no significant difference for both sides (p > 0.05). The mean volume of the right and left maxillary sinuses were 12.98±4.90 cm3 and 13.18±4.99 cm3, respectively. No significant difference between the volumes of both sides (p > 0.05) was found. The results showed no significant differences between the CB or NSD groups on both sides (p > 0.05). Conclusion: The two anatomical variations have no effect on the maxillary sinus volume. The open-source software ITK-SNAP is a valuable tool for volumetric analysis.